Efficient quality of service provisioning in the next generation internet - Siew, David Chee Kheong (2008)
PhD Thesis on "On Efficient Quality of Service Provisioning in the Next Generation Internet". Besides a comprehensive literature review on existing QoS provisioning techniques, we propose the so-called Flow-state-dependent Dynamic Priority Scheduling (FDPS) algorithm that provides Service Curves (SC) scheduling. By means of mathematical analysis, we show that the FDPS algorithm realizes the arrival and service curves SCS scheduling in a real network for per flow QoS provisioning.